2021
DOI: 10.1093/heapol/czab101
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the determinants of foetal alcohol spectrum disorder in South Africa: an intersectional perspective

Abstract: Foetal alcohol spectrum disorder (FASD) affects babies born to mothers who consume alcohol while pregnant. South Africa has the highest prevalence of FASD in the world. We review the social determinants underpinning FASD in South Africa and add critical insight from an intersectional feminist perspective. We undertook a scoping review, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews guidelines. Drawing from EBSCOhost and PubMed, 95 articles were screened, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Socioeconomic surveys conducted in the towns of Vanwyksvlei, Sutherland and Loeriesfontein between 2016 and 2019 found education and skill levels to be generally very low and the school dropout rate among teenagers alarmingly high (Walker & Vorster, in press). Respondents in all three towns identified alcohol and drug abuse and associated crime as major problemsas already noted, rates of alcoholism and foetal alcohol spectrum disorders are extremely high in this region (Olivier et al, 2016;De Jong et al, 2021). Worth noting is that these surveys did not find widespread interest in farming as a serious option, although some households expressed varying degrees of interest in accessing commonage land for grazing small herds, and a few individuals indicated an interest in land reform opportunities.…”
Section: Urban Karoomentioning
confidence: 75%
“…Socioeconomic surveys conducted in the towns of Vanwyksvlei, Sutherland and Loeriesfontein between 2016 and 2019 found education and skill levels to be generally very low and the school dropout rate among teenagers alarmingly high (Walker & Vorster, in press). Respondents in all three towns identified alcohol and drug abuse and associated crime as major problemsas already noted, rates of alcoholism and foetal alcohol spectrum disorders are extremely high in this region (Olivier et al, 2016;De Jong et al, 2021). Worth noting is that these surveys did not find widespread interest in farming as a serious option, although some households expressed varying degrees of interest in accessing commonage land for grazing small herds, and a few individuals indicated an interest in land reform opportunities.…”
Section: Urban Karoomentioning
confidence: 75%
“…Women facing often unbearable circumstances are left vulnerable to substance use as a means to cope or to forget (de Vries et al., 2016; Shrestha et al., 2018). Social relationships and norms strongly influence a women's relationship with alcohol (De Jong et al., 2021). A high level of social support has been shown to be protective against antepartum health risks including substance use (Racine et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Women are dependent on health services, the media, and the community to provide alcohol risk information in a way that is both accessible and understandable (Lyall et al., 2021). Stigma and discrimination are further barriers to treatment and support and may limit the effectiveness of such communication (Aspler et al., 2019; De Jong et al., 2021). Relationships between FASD, drinking behaviors, and historical and contemporary trauma have been reported in other countries with population groups of lower socio‐economic status, such as Australia and Canada (Fitzpatrick et al., 2015; Salmon, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…27,47 Intersectionality has been conceptualised, and implemented, in different ways in literature reviews. De Jong et al 53 used intersectionality as a framework during a scoping review to develop analysis and policy recommendations for foetal alcohol spectrum disorder in South Africa, framing intersecting oppressions from downstream individual factors to upstream factors including the colonial context, racism and policy history. Husain et al 54 hoped to select studies that used intersectionality as a testable theory on the impact of marginalisation across intersecting categories of demographics with regards to digital care, but found that the studies used descriptive, rather than explanatory analysis.…”
Section: Epistemological and Methodological Considerationsmentioning
confidence: 99%